A collagen extraction and deuterium oxide stable isotope tracer method for the quantification of bone collagen synthesis rates in vivo. Issue 10 (27th May 2021) - Civil, Rita; Brook, Matthew S.; Elliott‐Sale, Kirsty J.; Santos, Lívia; Varley, Ian; Lensu, Sanna; Kainulainen, Heikki; Koch, Lauren G.; Britton, Steven L.; Wilkinson, Daniel J.; Smith, Kenneth; Sale, Craig; et al.
Abstract: The development of safe and practical strategies to prevent weakening of bone tissue is vital, yet attempts to achieve this have been hindered by a lack of understanding of the short‐term (days‐weeks) physiology of bone collagen turnover. To address this, we have developed a method to quantify bone collagen synthesis in vivo, using deuterium oxide (D2 O) tracer incorporation techniques combined with gas chromatography pyrolysis isotope‐ratio mass spectrometry (GC‐ pyrolysis ‐IRMS). Forty‐six male and female rats from a selectively bred model ingested D2 O for 3 weeks. Femur diaphyses (FEM), tibia proximal (T‐PRO), and distal (T‐DIS) epiphyses‐metaphyses and tibia mid‐shaft diaphyses (T‐MID) were obtained from all rats after necropsy. After demineralisation, collagen proteins were isolated and hydrolysed and collagen fractional synthetic rates (FSRs) determined by incorporation of deuterium into protein‐bound alanine via GC‐ pyrolysis ‐IRMS. The collagen FSR for the FEM (0.131 ± 0.078%/day; 95% CI [0.106–0.156]) was greater than the FSR at T‐MID (0.055 ± 0.049%/day; 95% CI [0.040–0.070]; p < 0.001). The T‐PRO site had the highest FSR (0.203 ± 0.123%/day; 95% CI [0.166–0.241]) and T‐DIS the lowest (0.027 ± 0.015%/day; 95% CI [0.022–0.031]). The three tibial sites exhibited different FSRs ( p < 0.001). Herein, we have developed a sensitive method to quantify in vivo bone collagen synthesis and identified site‐specific rates of synthesis, which could be applicable to studies of human bone collagen turnover. Abstract : We have developed a method to quantify bone collagen synthesis in vivo, using D2 O in adult rodents combined with highly sensitive GC‐ pyrolysis ‐IRMS techniques. This method is ideally suited to the measurement of slow turnover proteins, such as collagen, and its high sensitivity will permit the application of D2 O loading protocols that are well tolerated in humans (i.e., 150 ml + 50 ml/week ‐1 ). Therefore, our D2 O GC‐ pyrolysis ‐IRMS approach has great potential applicability to study human bone collagen turnover.